JASMR 2006
DOI: 10.21000/jasmr06022289
|View full text |Cite
|
Sign up to set email alerts
|

SHORT-TERM ACID ROCK DRAINAGE CHARACTERISTICS DETERMINED BY PASTE pH AND KINETIC NAG TESTING: CYPRESS PROSPECT, NEW ZEALAND

Abstract: Abstract. The paste pH test (1 part solid: 2 parts water) is one method used to determine the acidic nature of a rock/soil sample. In conjunction with kinetic NAG testing a classification scheme has been developed for the Cypress Prospect within the Stockton coal mining region, West Coast, New Zealand. Samples having a paste pH of < 4.0 are considered potentially acid forming (PAF) and contain significant acidic sulfate salts (up to 30.1 kg H 2 SO 4 /t equivalent) that will immediately produce acid upon exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 8 publications
0
24
0
2
Order By: Relevance
“…For acid formation potential, the paste pH test is one of method used to determine the acidic nature of a rock/soil sample (Weber et al 2006). Although the paste pH is an instant measurement of acidity or alkalinity of the sample but it cannot provide quantitative result.…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For acid formation potential, the paste pH test is one of method used to determine the acidic nature of a rock/soil sample (Weber et al 2006). Although the paste pH is an instant measurement of acidity or alkalinity of the sample but it cannot provide quantitative result.…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
“…Although the paste pH is an instant measurement of acidity or alkalinity of the sample but it cannot provide quantitative result. The test was prepared by 1 g powder sample mixed with 20 ml deionized water, and then tested with a pH probe after 1 h. The paste pH results would initially indicate potential of acid mine drainage (Sobek et al 1978;Noll et al 1988;Weber et al 2006); however, quantitative static methods must be carried out to confirm this.…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
“…Paste pH was analyzed in duplicate with a pH meter (Metrohm Ltd., 704 pH Meter, Herisau, Switzerland) for all four batches of GLD according to Weber et al [23].…”
Section: Physical Characterizationmentioning
confidence: 99%
“…The FLT is effective because it rapidly dissolves these readily soluble phases providing a snapshot of the net or ''weathering'' ABA of the mine waste materials. Whereas other studies Weber et al, 2006) have previously shown that pH results from the paste test provide indication of short-term ABA potential of a mine waste sample, this study provides data showing that the use of either paste pH or 5-min FLT pH are effective at predicting not only the short-term, but also the long-term ABA behavior of weathered metal mining waste.…”
Section: Acid-base Accounting Resultsmentioning
confidence: 51%